UWU Tap Dengan Water Measurement dan Hydropower Berbasis IOT Sebagai Solusi Penghematan Air Dalam Berwudhu di Era Society 5.0 - Zulkhairiansah; Arbi Azizi Lubis, Reza; Fadilah, Aria; Syaputri, Kartika; Setiawan Lubis, Rifqi (Jurnal Etnik: Ekonomi-Teknik, 2024)
This research examines the problem of water use in the ablution process in Muslim communities in Indonesia, where around 90% of the population is Muslim. Water waste during ablution activities is a major concern, especially when the amount of water used per ablution is relatively high. There is also the problem of using manual ablution faucets which are less efficient and prone to damage. This condition is exacerbated by the clean water crisis in several areas, which emphasizes the importance of efficient water use. In order to overcome this problem, this research presents a solution in the form of UWU (Automatic Ablution) Tap, an automatic water tap with various innovative features. UWU Tap uses a proximity sensor to detect the part of the body performing ablution and utilizes the flow of ablution water as a source of electrical energy for the tap. In addition, this faucet is equipped with a flowmeter sensor and LCD screen to monitor water usage. There is also a web platform that allows monitoring and analysis of ablution water usage data. Trial results show that the UWU Tap can save up to 37% of water usage compared to manual ablution taps. The use of a mini generator and water usage indicator are additional advantages. In addition, this product can be mass produced at an affordable price, enabling its use in mosques, prayer rooms and other public facilities. This research makes a significant contribution to overcoming the problem of wasting water during ablution activities, as well as creating an efficient, innovative and affordable solution for the Muslim community in Indonesia.